Dynamics of interethnic relations in the assessments of residents of a multiethnic city (the case of Yakutsk) - Elena Yu. Shchegolkova (Historical Ethnology, 2024)
The article presents the results of the analysis of interethnic relations of the population of Yakutsk. The ideas existing in the public consciousness about the state of these relations in the republic and their problem areas are summarised. The state and dynamics of the urban ethnosocial situation and attitudes in interpersonal communication are diagnosed (using the case of the city of Yakutsk). The results of a representative sociological survey and expert interviews on topical issues of interethnic relations implemented in different years in the Republic of Sakha (Yakutia) have been analysed using the following indicators: assessment of interethnic relations, data on the attitude of citizens to people of other nationalities. Ethnically differentiated assessments of the interethnic interactions of the population of Yakutsk are presented based on their comparison with the opinion of the population of the region as a whole, as well as with the Yakut people living in rural areas and in certain regions of the republic. An analysis of the dynamics of assessments of interethnic relations by residents of Yakutsk shows that they were not stable. In five years, their character has changed from a fairly high tension to mostly favourable assessments. The alarming trends in the development of interethnic relations, identified in 2019–2021 in the context of the events in Triumph and Covid restrictions, have recently changed their vector towards benevolence against the background of increasing satisfaction with the financial situation of certain categories of the population. The assessments of interethnic relations by residents of Yakutsk at the regional and local levels practically do not differ and are generally similar to national ideas. The analysis confirmed the existence of differences in the development of interethnic relations in the urban and rural environments of the region. In cities, especially large ones, relationships are assessed as more complex, but the level of ethnic negativity is lower. The dynamics of ...